Optoelectronic Characterization of Natural Dyes in the Quest for Enhanced Performance in Dye-Sensitized Solar Cells: A Density Functional Theory Study - Pramesh Gunawardhana; Yashas Balasooriya; Murthi S. Kandanapitiye; Yuan-Fong Chou Chau; Muhammad Raziq Rahimi Kooh; Roshan Thotagamuge (Applied Sciences, 2023)
This study employs density functional theory (DFT) to evaluate the optoelectronic features of five natural dyes (cyanidin, delphinidin, pelargonidin, peonidin, and petunidin) in gas and ethanol phases for potential dye-sensitized solar cell (DSSC) applications. Calculations cover HOMO and LUMO energy levels, charge transfer potential gaps, and light absorption properties correlated with oscillator strengths. Photovoltaic aspects, including light-harvesting efficiency (LHE), electron injection efficiency (ΔGinject), regeneration efficiency (ΔGregen), open-circuit voltage (VOC), excited-state lifetime (τ), and the electronic coupling constant (|VRP|), were computed to assess DSSC suitability. DFT analysis reveals that cyanidin, delphinidin, and petunidin exhibit favorable LUMOs for efficient electron injection into the semiconductor’s conduction band. Cyanidin demonstrates a high quantum yield for light absorption. Delphinidin and petunidin act as effective light absorbers with high excitation energies and oscillator strengths, while petunidin and delphinidin display strong LHE, indicating excellent electron-donating capabilities. Peonidin shows promising ΔGinject despite needing more energy for injection. Pelargonidin excels in ΔGregen and |VRP|, enhancing DSSC performance. Petunidin and delphinidin exhibit a high VOC. Petunidin efficiently transmits energy through a large τ, while pelargonidin’s |VRP| confirms its potential as a favorable sensitizer. In summary, each dye possesses unique properties, and understanding them aids in selecting the most suitable dye for enhanced DSSC performance.